2022
DOI: 10.11005/jbm.2022.29.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of T-Score Spine-Hip Discordance in Patients with Osteoporotic Vertebral Compression Fracture

Abstract: Background: T-score discordance between the spine and hip is commonly observed when dual energy X-ray absorptiometry (DXA) is used to diagnose osteoporosis. However, information is scarce regarding the prevalence and risk factors for this problem in Korea. This study evaluated the prevalence of major/minor discordance and associated risk factors in elderly Korean patients with osteoporotic vertebral compression fractures (OVCFs).Methods: This study included 200 patients (37 men, 163 women) treated for thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The main reason may be that the morphological changes of the height or the kyphosis angle after surgery, the sheer force of the adjacent segments is increased, so that leading to increased risks of adjacent vertebral compression fracture. This result was also consistent with previous opinion reported by previous studies [32][33][34][35][36] . Subject to this study, we do not recommend for force the perfect recovery of vertebral height too much in the operation.…”
Section: Discussionsupporting
confidence: 94%
“…The main reason may be that the morphological changes of the height or the kyphosis angle after surgery, the sheer force of the adjacent segments is increased, so that leading to increased risks of adjacent vertebral compression fracture. This result was also consistent with previous opinion reported by previous studies [32][33][34][35][36] . Subject to this study, we do not recommend for force the perfect recovery of vertebral height too much in the operation.…”
Section: Discussionsupporting
confidence: 94%
“…[ 9 ] Otherwise, our previous study showed that LS discordance was main pattern (81.3%) in patients with an osteoporotic vertebral compression fracture. [ 10 ] It is notable because T-score of the spine is usually higher than that of the hip in the elderly over 70 years of age due to degenerative changes. [ 15 , 19 ] Considering the above results, clinicians need to know the possibility of discordance and type to predict osteoporotic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Thus it seems to be there are differences in pattern of discordance according to the fracture site or type. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this epidemiology study, multiple studies have reported a high prevalence of T -score discordance in populations with different ethnicities. 5 7 They have also attempted to identify the contributing factors. However, studies have only considered basic demographic data (e.g., age, sex, and body weight) and patient clinical history (e.g., menopause or smoking) and may have overlooked other variables that are highly correlated with bone health, such as muscle power, visceral adiposity percentage, and walking speed.…”
Section: Introductionmentioning
confidence: 99%